Historyczne uwarunkowania powstania i rozwoju rynków telefonii komórkowej w XX i XXI wieku - Plewczyński, Włodzimierz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article is focused on the presentation and analysis of two historical deter- minants that probably had the greatest impact on the rise and development of global mobile phone markets. On the one hand, this is the technical development of wireless telephony, which can also be seen as a space that provided a major impulse for political and legał changes in telecommunications. On the other hand, these political and legał changes associated with processes of liberalization in the world telecommunications have been described as the second fundamental factor.